Increased nuchal translucency and fetal outcomes: a population-based study in Thailand - Kuntharee Traisrisilp; Supatra Sirichotiyakul; Fuanglada Tongprasert; Kasemsri Srisupundit; Suchaya Luewan; Phudit Jatavan; Sirinart Sirilert; Theera Tongsong (Clinical and Experimental Obstetrics & Gynecology)
Background: To determine the association between increased nuchal translucency (INT) and fetal outcomes among Thai population. Methods: A prospective database of fetal Down syndrome screening project was accessed to enable retrieval of the records of any women with recorded NT measurements. The selected pregnancies were categorized into the INT group (>95th percentile) and the normal (<95th percentile) group. The effectiveness of NT for prediction of Down syndrome and hemoglobin Bart’s disease was also determined. Pregnancy outcomes were compared, also using multivariate analysis to correct the major confounders. Results: Out of 8225 NT measurements recorded, data from 7126 fetuses were available for analysis. These included 357 in the INT group and 6769 in the normal group. INT was significantly associated with Turner syndrome, Down syndrome, Edwards’ syndrome, Patau syndrome, cardiac defect and Hb Bart’s disease. After exclusion of fetal abnormalities, rates of abortion, low birth weight (LBW), preterm birth and intrauterine death (IUD) were significantly higher in the INT group, with adjusted odds ratio (95% CI) of 7.82 (7.48–13.66), 0.60 (0.42–0.86) and 5.10 (1.11–23.42), respectively. INT was effective in predicting Down syndrome with a sensitivity of 61.1% with a false positive rate of 5%. Conclusions: In addition to effectiveness in screening aneuploidy and cardiac defect, INT significantly increased the identification of risk of some diseases specific to a certain geographical area, for example Hb Bart’s disease in Thailand. Among the euploid fetuses in this study the rate of abortion, LBW, preterm birth and IUD were also significantly increased.